'Finding home': campus racial microclimates and academic homeplaces at a Hispanic-Serving Institution - Serrano, Uriel (Race, ethnicity and education, 2022)
Students do not uniformly feel welcome in university environments, and their experiences vary across race. Drawing on 19 interviews with Black and Latino men at a Hispanic-Serving Institution, this study demonstrates that participants perceive the campus racial climate at the organizational level differently. However, perceptions and experiences in microclimates converge and are informed by the lack of Black and Latinx faculty, the underrepresentation of Black students, and experiences with racial microaggressions. This study bridges prior research on microclimates and campus racial climates to advance the concept of campus racial microclimates. I also introduce the concept of academic homeplaces, which are campus racial microclimates that foster a sense of community and affirmation.